Low voltage high performance super class AB OTA design using SCCM and DTMOS with enhanced slew rate and DC gain. (July 2021) - Mahendra, Mihika; Kumari, Shweta; Gupta, Maneesha; Sangal, Ankur
Abstract: This paper presents two low voltage high performance super class AB Operational Transconductance Amplifiers (OTAs) along with the second stage. The proposed OTA-I implements self cascode current mirrors (SCCMs) as the active load to provide high output swing. And the flipped voltage followers (FVFs) based adaptive biasing technique for the differential input stage to provide an additional current boosting and offers significantly improved slew rate and dynamic characteristics. Proposed OTA-II is the DTMOS implementation of proposed OTA-I suitable for low voltage operation. It utilizes the body effect and offers a more enhanced performance with minimized power consumption. The small-signal analysis shows the improvements achieved in dc gain and gain-bandwidth product (GBW). The second-order universal MISO filter realized using the proposed OTAs validates its competency. The simulation results are obtained using Mentor Graphics Eldospice tool with TSMC 0.18 ​μm technology. The proposed OTA-I (±0.75 ​V) and the proposed OTA-II (±0.5 ​V) provides dc gain as 105.66 ​dB and 108.15 ​dB with greatly improved average slew rate by factor 216 to 339 and enhanced GBW by factor 16 to 120 with reduced power dissipation as compared to conventional class A OTA. Besides, it also provides an improvement in the common-mode rejection ratio (CMRR). The figure of merit of proposed OTAs is 9621 [(MHz).pF/mW] and 50322[(V/μs).pF/mW] respectively for the load capacitor of 10 ​pF, and shows significant improvement compared to prior work. To authenticate the robustness of proposed OTAs, Monte Carlo and Corner analyses done with Process-Voltage-Temperature variations.